Epigenetic control over the cell-intrinsic immune response antagonizes self-renewal in acute myeloid leukemia - Felipe-Fumero, Eloísa; Walter, Carolin; Frenz, Joris; Seifert, Franca; Alla, Vijay; Söhngen, Thorben; Angenendt, Linus; Hartmann, Wolfgang; Wolf, Sebastian; Serve, Hubert; Oellerich, Thomas; Lenz, Georg; et al. (Blood, 2024)
Epigenetic modulation of the cell-intrinsic immune response holds promise as a therapeutic approach for leukemia. However, current strategies designed for transcriptional activation of endogenous transposons and subsequent interferon type-I (IFN-I) response, show limited clinical efficacy. Histone lysine methylation is an epigenetic signature in IFN-I response associated with suppression of IFN-I and IFN-stimulated genes, suggesting histone demethylation as key mechanism of reactivation. In this study, we unveil the histone demethylase PHF8 as a direct initiator and regulator of cell-intrinsic immune response in acute myeloid leukemia (AML). Site-specific phosphorylation of PHF8 orchestrates epigenetic changes that upregulate cytosolic RNA sensors, particularly the TRIM25-RIG-I-IFIT5 axis, thereby triggering the cellular IFN-I response-differentiation-apoptosis network. This signaling cascade largely counteracts differentiation block and growth of human AML cells across various disease subtypes in vitro and in vivo. Through proteome analysis of over 200 primary AML bone marrow samples, we identify a distinct PHF8/IFN-I signature in half of the patient population, without significant associations with known clinically or genetically defined AML subgroups. This profile was absent in healthy CD34+ hematopoietic progenitor cells, suggesting therapeutic applicability in a large fraction of patients with AML. Pharmacological support of PHF8 phosphorylation significantly impairs the growth in samples from patients with primary AML. These findings provide novel opportunities for harnessing the cell-intrinsic immune response in the development of immunotherapeutic strategies against AML.
Gesehen am 26.11.2024